Correlation of left atrial function and pulmonary edema in patients with left heart failure on cardiopulmonary ultrasonography - Li, Hong; Hu, Ping-Xiang; Chen, Jian (Frontiers in Cardiovascular Medicine, 2023)
Objective: Patients with heart failure with pulmonary edema may have declining left atrial (LA) function. Left atrial strain (LAS) imaging enables quantitative assessment of LA function. The aim of this prospective study was to assess the LA function and pulmonary edema in patients with heart failure evaluated by cardiopulmonary ultrasonography. Methods: Two-dimensional speckle-tracking echocardiography for LAS was performed in 115 consecutive patients with congestive heart failure. A semiquantitative B-lines score of pleural effusions was derived by pulmonary ultrasound almost at the same time by combined cardiopulmonary ultrasound. Results: Compared with those who did not have pulmonary edema, patients with pulmonary edema had lower LAS (LASreservoir, 21.5±4.9% vs 9.2±3.7% [P<0.001]; LASconduit, 10.7±3.5% vs 5.1±2.1% [P<0.001]; LASpump, 11.3±5.4% vs 4.0±2.7% [P<0.001]), lower LVEF, TAPSE; and higher SPAP, E/e′, larger LA, LV, RV; more severe MR. However, there were no signiﬁcant between-group differences with respect to sex and body surface area. In patients with pulmonary edema, B-lines score was independently associated with LASreservoir (R= -0.71, P<0.001); LASpump (R= -0.66, P<0.001) and LASconduit (R= -0.56, P<0.001). On multiple linear regression, decreased LASreservoir (beta= -0.61, B= -0.71, P<0.001) and elevated SPAP (beta= 0.31, B= 0.13, P=0 .01) were significantly associated with B-lines score in heart failure. Conclusion: Declining LA function, especially the reservoir function, assessed by speckle-tracking echocardiography is related to the degree and occurrence of pulmonary edema in patients with left heart failure.